Pharynx Diagnosis and Treatment - Zhou, Xiaoying; Zhang, Zhe (IntechOpen, 2021)
Pharynx - Diagnosis and Treatment provides scientific views from international experts on the latest studies and consensus in pharynx diseases, in particular pharyngeal tumors, including oropharyngeal carcinoma, nasopharyngeal carcinoma, hypopharyngeal carcinoma, and others. The book also addresses non-tumoral pharyngeal diseases such as nasopharyngeal angiofibroma and obstructive sleep apnea. The chapters present guidelines and standards commonly used in clinics for the pharynx diseases mentioned, as well as new updates covering recent scientific findings and translational research on the approaches of diagnosis and treatment.